Stars with fast galactic rotation observed in gaia TGAS: a signature driven by the Perseus arm? - Hunt, Jason A. S.; Grand, Robert J. J. (Monthly notices of the Royal Astronomical Society. Letters, 2016)
We report on the detection of a small overdensity of stars in velocity space with systematically higher Galactocentric rotation velocity than the Sun by about 20 km s−1 in the Gaia Data Release 1 Tycho-Gaia astrometric solution data. We find these fast Galactic rotators more clearly outside of the Solar radius, compared to inside of the Solar radius. In addition, the velocity of the fast Galactic rotators is independent of the Galactocentric distance up to R − R0 ∼ 0.6 kpc. Comparing with numerical models, we qualitatively discuss that a possible cause of this feature is the co-rotation resonance of the Perseus spiral arm, where the stars in the peri-centre phase in the trailing side of the Perseus spiral arm experience an extended period of acceleration owing to the torque from the Perseus arm.
Gesehen am 23.10.2017